Encouraging Students to Enhance Their Listening Performance - Hernandez-Ocampo Sonia Patricia; Vargas María Constanza (Universidad Nacional de Colombia, 2013)
Spanish-speaking students constantly complain about the difficulty they have comprehending spoken English. It seems teachers do not often provide them with strategies to alleviate that. This article reports on a pedagogical experience carried out at a Colombian university to help pre-service teachers at an intermediate level of English to improve their aural comprehension. The students were given the task of designing listening activities to be worked on as micro-teaching sessions and were asked to describe their experience by answering a survey. The results showed that students developed the ability to think critically since they needed to make the best decisions regarding the audio level and the design of the activities. They also appeared to have become more autonomous as they realized they could be responsible for their improvement in listening. Additionally, there were evident changes in the teachers' roles. Es común que los hablantes de español se quejen de su comprensión oral en inglés. Parece que los profesores no siempre dan a sus estudiantes estrategias para mejorar al respecto. En este artículo se describe la experiencia pedagógica desarrollada en una universidad colombiana con el propósito de ayudar a los estudiantes de inglés intermedio de una licenciatura a mejorar su comprensión auditiva. Se pidió a los estudiantes desarrollar actividades de escucha para ser trabajadas en sesiones de microenseñanza y describir su experiencia, contestando una encuesta. Los resultados evidenciaron que los estudiantes desarrollaron su pensamiento crítico en la medida que necesitaban tomar decisiones con respecto al nivel de dificultad del audio y al diseño de las actividades mismas. También se mostraron más autónomos por cuanto se hicieron conscientes de su responsabilidad en el mejoramiento de su comprensión oral. Adicionalmente, se dieron cambios en los papeles del profesor.